Lepi Straw / Mohd Sharmizam Ishak ... [et al.] - Ishak, Mohd Sharmizam; Ibrahim, Mohd Azhar; Zamri, Inna Farina; Mat Zin, Noor Hidayu (2019)
Plastic pollution is when plastic has gathered in an area and has begun to negatively impact the natural environment and create problems for plants, wildlife, and even the human population. Often this includes killing plant life and posing dangers to local animals. According to a report published by the Ellen MacArthur Foundation, if the current rate of plastic pollution continues, there will be more plastic in the oceans than there are fish by the year 2050. Plastic straw is major pollution in the world, though at first this small straw may not seem like a lot, when its usage is added up, plastic straws create a big problem for the environment. Plastic free alternatives already do exist in the market which are eco-friendly and sustainable. So there is a raise in demand for new alternatives to solve the plastic straw pollution. In order to overcome this problem, many company trying to do their best to cope with this issue. Many suggestion such as paper straw, rice grain straw, metal straw and bamboo straw has come to the market. Our company, taking this opportunity by taking a grass straw which has been innovated by a Vietnamese man namely Tran Minh Tien. Tran has shown how a certain type of grass named Lepironia articulata (also known as Grey sedge) that is dominantly found around the Mekong Delta in Vietnam which is being converted into drinking straws. Apart from this, the straw is just a plain straw. Our company taking these model of straw into a next level of straw by improvising it with a new features.